Editorial commentaryPneumacephalus after Influenza virus infection and its implication to modern anterior skull base surgery - Sandu, Nora; Schaller, Bernhard (Archives of Medical Science, 2008)
Commentary on Widespread subarachnoidal pneumocephalus development as a complication of influenza: a case report Dilcan Kotan Arch Med Sci 2008; 4, 4: 471–473